Mediação cultural na Biblioteca Universitária por meio de mapeamento cognitivo - Soares, Maria Giovana (2023)
Research on cultural mediation in the context of the university library is incipient. The few studies reveal that cultural activities are carried out sporadically, as well as they do not report on the planning for the systematic execution of cultural mediation practices in this environment. Thus, an instrument that can be used to support the planning of cultural mediation actions is cognitive mapping, in order to develop cultural mediation activities based on the cognitive profile (perception, attention and focus) of the community of users participating in the actions performed. Therefore, this research sought to solve the question of how to plan cultural mediation actions in a university library using the cognitive mapping instrument. The general objective was to evaluate the planning of cultural mediation actions by mapping the cognitive profile of users of the Central Library (BC) of SIB/Ufes. Specifically, we tried to examine the cultural mediation activities adopted by the Central Library; map the cognitive profile of Library users; and establishing cultural mediation actions based on the users' cognitive profile with the evaluation of the process. Therefore, it was decided to develop an applied and exploratory social research with a mixed methods approach. As methodological procedures, a bibliographic survey was used to build the theoretical framework and develop the cognitive mapping; as well as the case study, for analysis of the research object, that is, the cultural mediation situated in a real environment, the case of the Central Library of SIB/Ufes. Linked to the case study, documentary research was adopted, which demonstrated that BC does not systematically develop cultural activities; and participant research, which allowed the researcher to plan and participate in the cultural activity and observe the behavior, expressions and emotions of the researched individuals. For further data collection, cognitive mapping was applied to group 1 - mapped, which enabled the planning and execution of the cultural activity based on the cognitive profile of this group. After the cultural activity, the questionnaire was applied to group 1 – mapped and also to group 2 – not mapped. For data analysis, percentage calculation, mode, mean and median were used. The results indicated that the elaboration of the planning of the activity based on the first mapping was adequate, in a way that it awakened the perceptive and attentional process, and the focus of both groups. It was concluded by highlighting that the research can contribute to new debates on the subject in the context of Information Science and for the production of new studies contemplating cultural mediation in the university library space, since it is a subject little explored in this space.